Respuesta :
Answer:
x2 + 100 = (x + 10i)(x − 10i)
x2 + 36 = (x + 6i)(x − 6i)
16x2 + 9 = (4x + 3i)(4x − 3i)
Step-by-step explanation:
Edmentum Answer
The factors of the expressions have been determined as ( x +10i) ( x -10i) , ( x +6i) (x-6i) , (4x + 3i) ( 4x - 3i)
What is an Expression ?
An expression is a mathematical statement consisting of variables , constants and mathematical operators .
The expression given in the question is
x² + 100
x² + 36
16x²2 +9
by the identity a² -b² = ( a+b)(a-b)
The expressions can be written as
( x² - ( 10i)²) , (x² - ( 6i)²) , ( (4x)² - ( 3i)²)
It is known that i² = -1
Therefore here the expressions can be written as
( x² - ( 10i)²) = ( x +10i) ( x -10i)
(x² - ( 6i)²) = ( x +6i) (x-6i)
( (4x)² - ( 3i)²) = (4x + 3i) ( 4x - 3i)
Therefore the factors of the expressions have been determined.
To know more about Expression
https://brainly.com/question/14083225
#SPJ2